2009
DOI: 10.1182/blood-2008-07-144485
|View full text |Cite
|
Sign up to set email alerts
|

The role of indoleamine 2,3-dioxygenase in the induction of immune tolerance: focus on hematology

Abstract: The regulation of the interaction between the immune system and antigens, which may lead to the induction of immune tolerance, is critical both under physiologic conditions and in different pathological settings. In the past few years, major strides have been made in our understanding of the molecular and cellular bases of this process. Novel IntroductionIndoleamine 2,3-dioxygenase (IDO) is an intracellular hemecontaining enzyme that catalyzes the initial rate-limiting step in tryptophan degradation along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
199
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(214 citation statements)
references
References 92 publications
7
199
0
8
Order By: Relevance
“…In this sense, emergent data suggest that DCs heterogeneity and activation states may be involved in autoimmune response either by a dysregulation of DC maturation towards their chronic activation and their cytokine secretion or by defective induction and maintenance of antigen-specific peripheral T-cell tolerance. Thus, abnormalities reported in SLE patients may represent DC-intrinsic defects and/or result of secondary defects such an imbalance of cytokine signals that could generate directly prime of autoreactive T cells, or fail to prime regulatory T-cell subsets, or even shift a Th1/Th2 balance to an unfavourable outcome [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, emergent data suggest that DCs heterogeneity and activation states may be involved in autoimmune response either by a dysregulation of DC maturation towards their chronic activation and their cytokine secretion or by defective induction and maintenance of antigen-specific peripheral T-cell tolerance. Thus, abnormalities reported in SLE patients may represent DC-intrinsic defects and/or result of secondary defects such an imbalance of cytokine signals that could generate directly prime of autoreactive T cells, or fail to prime regulatory T-cell subsets, or even shift a Th1/Th2 balance to an unfavourable outcome [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This effect could be exerted either through cell-tocell contact or by the release of soluble factors. 6,7 Moreover, the conditioning regimen and/or the occurrence of GvHD may sustain an inflammatory response in the BM which may further interfere with the normal hematopoiesis. 8 Notably, inflammation has been associated with promotion and progression of solid tumors, and may correlate with a poor prognosis.…”
Section: -5mentioning
confidence: 99%
“…IDO, which is inducible by various inflammatory stimuli, is widely distributed in various immune and nonimmune cell types, and downregulates adaptive immune response and inflammation as well. [7][8][9][10] Recently, we have shown that IDO plays a significant role in the impaired adaptive immunity that characterizes HD patients. 11 Considering that inflammation contributes to atherosclerosis progression in HD patients, 12 evaluation of a possible role of this immunomodulatory enzyme is interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Serum interleukin-6 (IL-6) and C-reactive protein (CRP) were also measured because inflammation usually accompanies HD, [20][21][22] has been incriminated for atherosclerosis progression in this population, 12 and upregulates IDO. 7,8 …”
Section: Introductionmentioning
confidence: 99%